2014
DOI: 10.1109/tnet.2014.2309014
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing Space Explosion in High-Speed Regular Expression Matching

Abstract: Abstract-Network intrusion detection and prevention systems commonly use regular expression (RE) signatures to represent individual security threats. While the corresponding DFA for any one RE is typically small, the DFA that corresponds to the entire set of REs is usually too large to be constructed or deployed. To address this issue, a variety of alternative automata implementations that compress the size of the final automaton have been proposed such as XFA and D 2 FA. The resulting final automata are typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Patel et al . has found another drawback of automata construction algorithm where multiple NAFs are joined into a large DFA and then minimize it. That leads to an expensive subset construction from NFAs to DFAs for large NFAs and maybe a small final minimized DFA cannot be generated because of the failure of subset construction.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Patel et al . has found another drawback of automata construction algorithm where multiple NAFs are joined into a large DFA and then minimize it. That leads to an expensive subset construction from NFAs to DFAs for large NFAs and maybe a small final minimized DFA cannot be generated because of the failure of subset construction.…”
Section: Related Workmentioning
confidence: 99%
“…Compared with D 2 FA, A-DFA results in at most 2N.k C 1/=k state traversals when processing an input string of length N, k being a positive integer, and yields a 10fold improvement in compression ratio. Patel et al [10] has found another drawback of automata construction algorithm where multiple NAFs are joined into a large DFA and then minimize it. That leads to an expensive subset construction from NFAs to DFAs for large NFAs and maybe a small final minimized DFA cannot be generated because of the failure of subset construction.…”
Section: Related Workmentioning
confidence: 99%
“…Existing proposals targeting DFA-based solutions have focused on two aspects: (i) designing compression schemes aimed at minimizing the DFA memory footprint; and (ii) devising new automata to alternate DFAs in case of state explosion. Alphabet reduction [5,[22][23][24], run-length encoding [5], default transition compression [22,25], state merging [7] and delta-FAs [26] fall in the first category, while multiple-DFAs [5,6], hybrid-FAs [7], history-based-FAs [8], XFAs [9], counting-FAs [10], and JFAs [11] fall in the second category. All of these solutions, however, have been designed to operate on reassembled packet streams.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Most studies have focused on compression technologies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] to restrain the DFA expansion problem. Classical compression algorithms such as D FA [ 25 ] and A-DFA [ 26 ] were devised to reduce the space cost of DFA with performance guarantees.…”
Section: Introductionmentioning
confidence: 99%